Correlações entre a interleucina IL-1β e IL-8 com fatores antropométricos e bioquímicos em adolescentes com sobrepeso e obesidade - Fonseca, Gisele Almeida Amaral (2016)
Obesity has been described as an important contributing factor to the development of cardiovascular disease. However, there is no consensus on exactly how adolescents are affected by this metabolic disorder. The occurrence of future cardiovascular events is only performed in adults over 20 years old, demonstrating the difficulty in assessing the influence of potential risk factors in the youth population. The aim of this study was to evaluate and correlate anthropometric values, biochemical parameters and the expression of pro-inflammatory cytokines in adolescents from 14 to 18 years old. The adolescents divided into three groups: normal weight, overweight or obese according to their body mass index (BMI). The study included 96 adolescents enrolled in public and private schools in the city of Barra do Garças- MT. Analyses of anthropometric, blood pressure, biochemical parameters and profile of proinflammatory interleukins (IL) expression, such as, [IL-1β, IL-6, IL-8, IL-12 and tumor necrosis factor (TNF -α)] were performed in adolescents serum. The main data observed in this study were: increase in anthropometric factors such as weight, BMI, body fat percentage and waist circumference in overweight or obese; increase in systolic blood pressure and diastolic levels in the obese group; increase in blood glucose, triglycerides, total cholesterol, VLDL, LDL in the overweight group and decreased HDL in overweight and obese; low agglutination of C-reactive protein in all the groups; IL-1β expression and IL-8 increased current in the overweight and obese group, as well as a trend of increase in IL-6 and TNF-α in these groups; Positive correlations between the expression of IL-1β to IL-8 and TNF-α; and a positive correlation between IL-6 and IL-8; and inverse correlation between the expression of IL-6 and IL-12. Additionally, significant positive correlations were found between both IL-1β, as well as IL-8 with anthropometric and biochemical parameters The increased expression of IL- 1β and IL -8 as well as the correlations observed between these cytokines and other factors warrant the idea that changes in anthropometric , metabolic and immunological profiles should not be overlooked in adolescents, and these factors together, may favor the early development of cardiovascular disease in young adults.